Association of genotype of POU1F1 intron 1 with carcass characteristics in crossbred pigs - Kim, Gye-Woong (J Anim Sci Technol, 2014)
This study was carried out to investigate the association of POU1F1 (POU domain, class 1, transcription factor 1, Pit1, renamed as POU1F1) gene with backfat thickness (mm), carcass weight (kg), pH, and color values (L(*), a(*), b(*)) in crossbred pigs (Landrace x Yorkshire x Duroc). Frequency of the AA genotype indel was at the highest level (66.67%). Frequency of A allele (0.81) was higher than that of b allele (0.19). This population followed Hardy-Weinberg equilibrium. Carcass weights and a(*) values of the three genotypes were all significantly different (p < 0.05), respectively. However, backfat thickness, L(*), b(*), visual color, and pH of the three genotypes were not significantly different (p > 0.05). Visual color was negatively correlated with L(*) (r = -0.521) and b(*) (r = -0.390) values, L(*) value was correlated with b(*) (r = 0.419) value, and a(*) value was positively correlated with b(*) (r = 0.612) value. These results indicate that the POU1F1 gene affected carcass weight and meat redness.